Hydromagnetic radiative effect on water, kerosene based on single walled carbon nanotubes induced by a stretching/shrinking sheet with viscous-ohmic dissipation - Ilyasak, Mohd Qhushairi (2018)
The flow and heat transfer characteristics of radiative magnetohydrodynamic convection boundary layer flow of nanofluids over a nonlinear stretching/shrinking sheet in the presence of viscous dissipation, thermal radiation and Ohmic heating is investigated numerically.The similarity transformation reduces the time-independent boundary layer equations for continuity, momentum and energy into a set of coupled ordinary differential equations. The obtained governing equations have been solved numerically by using similarity transformation method with shooting technique and the analysis for the problem are evaluated by using MAPLE 2016. The influence on the velocity and temperature are presented both in tabular and graphical forms for various parameter such as magnetic field parameter (M), thermal radiation parameter (N), nonlinear parameter (m), Richardson number (RI), heat source parameter (), heat sink parameter (